Analysis of Indonesia's International Trade and Its Influencing Aspects - Sartika (Synergisia, 2024)
This study examines the dynamics of international trade in Indonesia and the factors influencing it. The researcher adopts a descriptive approach to elucidate the evolution of international trade and a verification method to identify variables impacting it. Secondary data spanning from 2003 to 2019 serves as the primary data source. The analysis employs multiple regression techniques. The findings reveal that international trade in Indonesia experienced fluctuations during the study period, largely driven by changes in oil and gas prices as well as non-oil commodity prices. Notably, growth in Indonesia's international trade is predominantly observed in the non-oil and gas sector. Consequently, the Indonesian government has devised strategies to support exporters in this sector through various incentives.The study identifies several factors affecting international trade, including exchange rates, inflation rates, government effectiveness, and trade openness. Simultaneously, these factors collectively influence international trade dynamics. However, the analysis indicates that inflation rate, government effectiveness, and trade openness significantly impact international trade, whereas the exchange rate factor exhibits no discernible effect